Galaxy Evolution in Clusters - Ruggiero, Rafael (2018)
In this thesis, we aim to further elucidate the phenomenon of galaxy evolution in the environment of galaxy clusters using the methodology of numerical simulations. For that, we have developed hydrodynamic models in which idealized gas-rich galaxies move within the ICM of idealized galaxy clusters, allowing us to probe in a detailed and controlled manner their evolution in this extreme environment. The main code used in our simulations is RAMSES, and our results concern the changes in gas composition, star formation rate, luminosity and color of infalling galaxies. Additionally to processes taking place inside the galaxies themselves, we have also described the dynamics of the gas that is stripped from those galaxies with unprecedented resolution for simulations of this nature (122 pc in a box including an entire 1e14 Msun cluster), finding that clumps of molecular gas are formed within the tails of ram pressure stripped galaxies, which proceed to live in isolation within the ICM of a galaxy cluster for up to 300 Myr. Those molecular clumps possibly represent a new class of objects; similar objects have been observed in both galaxy clusters and groups, but no comprehensive description of them has been given until now. We additionally create a hydrodynamic model for the A901/2 multi-cluster system, and correlate the gas conditions in this model to the locations of a sample of candidate jellyfish galaxies in the system; this has allowed us to infer a possible mechanism for the generation of jellyfish morphologies in galaxy cluster collisions in general.